Effects of Ecological Restoration Using Non-Native Mangrove Kandelia obovata to Replace Invasive Spartina alterniflora on Intertidal Macrobenthos Community in Maoyan Island (Zhejiang, China) - Qiuxuan Wang; Carlos Duarte; Li Song; George Christakos; Susana Agusti; Jiaping Wu (Journal of Marine Science and Engineering, 2021)
Spartina alterniflora has extensively invaded the coastline of China, including in Maoyan Island of Zhejiang Province. Ecological restoration has been conducted using non-native mangrove Kandelia obovata to replace S. alterniflora in an attempt to restore the impacted intertidal zones. To illustrate the ecological effectiveness of the restoration projects, macrobenthos communities were studied among different habitats within the restored areas, including one non-restored S. alterniflora marsh (SA) and three differently-aged restored K. obovata stands planted in 2003, 2009, and 2011 respectively (KF14, KF8, and KF6). Besides, one unvegetated mudflat (MF) adjacent to the non-restored S. alterniflora marsh and one K. obovata forest transplanted in 2006 (RKF) at a previously barren mudflat without invasion history of S. alterniflora were set as reference sites. A total of 69 species of macrobenthos were collected from Maoyan Island, and the species richness was dominated by gastropoda (23 species), polychaeta (18 species), and malacostraca (16 species). There was no significant difference between the six sites in terms of the abundance of macrobenthos, with the average values of abundance peaking in KF6 (734.7 ind m−2) and being lowest in RKF (341.3 ind m−2). The six sites had significant differences in terms of the biomass of macrobenthos. The KF8 site contained the highest average biomass (168.3 g m−2), whereas the MF site had the lowest (54.3 g m−2). The Shannon-Wiener diversity index and Pielou’s evenness index of the macrobenthos did not exhibit significant differences among the six sites. However, the results of permutational multivariate analysis of variance (PERMANOVA) revealed significant spatial differences in the macrobenthos community structure between the sites. Since KF14 shared a similar macrobenthos community structure with RKF, while representing a strikingly different structure from SA, we infer that ecological restoration using K. obovata can restore the macrobenthos community to resemble to a normally planted K. obovata forest about 15 years after restoration.